SWOT Analysis As A Strategy To Improve Competitiveness In PT Trans Antar Nusabird (Cititrans Travel) - Wala Erpurini (Jurnal Mantik, 2021)
This research aims to identify the strengths, weaknesses, opportunities and threats that the company has and to know the position of PT. Trans AntarNusabird in analysts is SWOT as well as to know the marketing strategy in accordance with the position of PT. Trans AntarNusabird in marketing its products, based on the company's position in SWOT analysis. This type of research is descriptive qualitative, with the data collection method used is primary data and secondary data, the population in this study is marketing manager of PT Trans AntarNusabird. Data analysis methods used in this study are SWOT analysis (Strenghts Weakness, Opportunities, Threats), IFAS Table (Internal Strategic Factor Analysis Summary) and EFAS (External Strategic Factor Analysis Summary) table that is clarified with SWOT Matrik to determine alternative strategies based on the results of analysis of internal and external strategic factors of the company.The conclusion of this research is SWOT Analysis can be used as a consideration in setting strategies on PT. Trans Inter Nusabird. From weighting analysis, ifas and EFAS rating and score obtained the number of scores at strength factor (S) 1.80, weakness factor (W) 0.68, opportunity factor (O) 1.52 and threat factor (T) of 0.68. The difference between IFAS and EFAS is obtained pt position. Trans AntarNusabird in quadrant 1 is an aggressive position. The company's Marketing Manager chose an alternative market development strategy by opening a new Shuttle Point in Lampung and KertaJati Airport and adding travel facilities in order to provide satisfaction and desire for the customers of PT Trans AntarNusabird.